Primer on Formation and Evolution of Hydrogen-Deficient Central Stars of Planetary Nebulæ and Related Objects - Marcelo M. Miller Bertolami (Galaxies, 2024)
We present a brief review of the formation and evolution of hydrogen-deficient central stars of planetary nebulae. We include a detailed description of the main observable features of both the central stars and their surrounding nebulae and review their main classifications. We also provide a brief description of the possible progenitor systems of hydrogen-deficient central stars as well as of transients, which are closely connected to the formation of these stars. In particular, we offer a detailed theoretical explanation of the main evolutionary scenarios, both single and binary, which is devised to explain these stars and nebulae. Particular emphasis is made in the description of the so-called born again scenario, their quantitative predictions, and uncertainties. Finally, we discuss the pros and cons of both binary and single evolution channels, draw some conclusions, and discuss open questions in the field.